PEER TUTORING IN THE ELEMENTARY CLASSROOM: PUTTING (A) THEORY INTO PRACTICE - Russo, James Anthony (McGill Journal of Education / Revue des sciences de l'éducation de McGill)

(untitled) (Faculty of Education, McGill University, 2018)
This essay explores how elementary school teachers can support students in becoming effective peer tutors. Drawing on the author’s personal experience as an elementary educator and researcher, it discusses how cognitive load theory can be used to generate a framework to support practicing teachers in implementing peer tutoring in their own classrooms. The framework presented is particularly relevant to well-structured learning domains, such as mathematics.